Lifelong learning as a governing technique of subjectivation from the perspective of the discourse of hope and fear - Chiang, Tien-hui; Thurston, Allen; MacKenzie, Alison (Frontiers in Political Science, 2024)
Neoliberal governmentality highlights that the mode of governing technologies has moved from government towards governance in modern society. Accordingly, as the self becomes the nexus between social control and self-regulation, configuring selfknowledge is mainly achieved through subjectivation, as argued by M. Foucault. The OECD's PISA program implicitly carries out this technique by holding teachers responsible for national prospects through its assumption of a close linkage between teaching quality and human capital. More importantly, PISA data facilitates international comparisons and rankings by which the international competitiveness of its participants can be identified and categorized. Unsurprisingly, those member countries/regions classified in the first tier are confident of their prospects for future economic growth in contrast with those ranked below the average, which are unable to escape from a state of fear engendered by their assumed lack of economic prospects.Teachers thus become the subject and object of educational reforms. Teachers need to improve their teaching quality through professional development to eliminate the stigma of being viewed as social burdens. The discourses of hope and fear set in motion by PISA thus turn lifelong learning into a powerful means of facilitating the government to fabricate teachers' subjectivity. This is the art of subjectivation, commanding teachers to perform as enterprising subjects who are dedicated to contributing to social progression through good teaching quality, which is perceived as the gateway for them to bring honor upon themselves.